Vigabatrin-Induced Seizures in Angelman Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Four children with Angelman syndrome (AS) showed worsening of seizures after introduction of vigabatrin (VGB), at the University Children's Hospital, Zurich, Switzerland.